BLURRING THE BOUNDARIES: THE EAST-WEST PREDICAMENT IN PAMUK’S A STRANGENESS IN MY MIND - Brameswari, Catharina (International Journal of Humanity Studies (IJHS), 2023)
This research focuses on Orhan Pamuk’s A Strangeness in My Mind. Since the Ottoman Empire, a modernity that is represented by the West has become a threat and seduction. Due to the issue, this research is conducted to highlight the transformation of İstanbul, analyse Turkey’s political agenda which enormously affects İstanbul and its citizens’ identity formation process, and investigate the result of the East-West predicament towards the main characters. This research is a descriptive qualitative method which employs Homi Bhabha’s discourse on Postcolonialism to uncover the predicament of the oscillation. The findings unveil 1) how İstanbul’s cosmopolitanism and uniqueness have disappeared bringing such a grieve towards the life of the citizens; 2) the ambivalence that is caused by both Atatürk and Erdoğan’s political agendas; and 3) the east-west oscillation which has led to melancholy and confusion. In addition, Mevlut’s strange mind is a bridge that tries to connect his friends and relatives who have different political views. Importantly, he also tries to blur the boundaries and promote tolerance towards various groups, religions, cultures, and traditions.